Clinical trial with liposomal amphotericin B (AMBISOME®) for American Visceral Leisshmaniais (AVL) - Viana, Graça Maria de Castro (2009)
Federal University of Maranhão. Nucleus of Tropical Pathology and Social Medicine. Department of Pathology. São Luis, MA, Brasil